Reparations and anti-Black racism: a criminological exploration of the harms of slavery and racialized injustice - Nurse, Angus (Bristol University Press, 2022)
"The Black Lives Matter movement has exposed the state violence and social devaluation that Black populations continue to suffer. Police shootings and incarceration inequalities in the US and UK are just two examples of the legacy of slavery today. This book offers a criminological exploration of the case for slavery and anti-Black racism reparations in the context of the enduring harms and differential treatment of Black citizens. Through critical analysis of legal arguments and reviewing recent court actions, it refutes the policy perspectives that argue against reparations. Highlighting the human rights abuses inherent to and arising from slavery and ongoing racism, this book calls for governments to take responsibility for the impact of ongoing racialized injustice."-- from publisher's website